The influence of interests, attitudes, and knowledge on entrepreneurial skills of Hamzanwadi University students - Muhammad Ali; Nurji Nurji (Journal of Enterprise and Development (JED), 2021)
The purpose of this study was to examine the effect of interests, attitudes, and knowledge on the entrepreneurial skills of Hamzanwadi University students. The analysis technique used in this research is Structural Equation Modeling (SEM) analysis, using a saturated sample, that is, the number of population is equal to the number of samples. The results of this study indicate that the interest variable has no significant effect on entrepreneurship skills seen from the observation t value (0.032) < t-table (1.98), then the attitude variable has a significant effect on entrepreneurship skills because the observation t value (0.232)> t-table (1.98), and the knowledge variable has a significant effect on entrepreneurial skills as seen from the observation t value of (0.267)> t-table (1.98).